2012
DOI: 10.1088/0004-637x/755/1/1
|View full text |Cite
|
Sign up to set email alerts
|

BURST FLUENCE DISTRIBUTIONS OF SOFT GAMMA REPEATERS 1806–20 AND 1900+14 IN THEROSSI X-RAY TIMING EXPLORERPCA ERA

Abstract: We study the fluence distributions of over 3040 bursts from SGR 1806−20 and over 1963 bursts from SGR 1900+14 using the complete set of observations available from the Rossi X-Ray Timing Explorer/Proportional Counter Array through 2011 March. Cumulative event distributions are presented for both sources and are fitted with single and broken power laws as well as an exponential cutoff. The distributions are best fitted by a broken power law with exponential cutoff; however the statistical significance of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
7
16
1
Order By: Relevance
“…This may naturally occur if the mean energy in such outflows is comparable to the radiative energy observed from these bursts. For the latter, the distribution is compatible with dN/dE ∝ E −5/3 (where N is the number of bursts and E is their radiated energy) expected for self-organized criticality (e.g., Cheng et al 1996;Gögüş et al 1999Gögüş et al , 2000Prieskorn & Kaaret 2012). This might suggest that the total energy output (which scales as E 2 dN/dE) is dominated by the largest events -the rare giant flares (although it is possible that such giant flares may comprise a separate component that is not the high energy tail of the self-organized critical phenomenon and are isolated events).…”
Section: Discussionsupporting
confidence: 66%
“…This may naturally occur if the mean energy in such outflows is comparable to the radiative energy observed from these bursts. For the latter, the distribution is compatible with dN/dE ∝ E −5/3 (where N is the number of bursts and E is their radiated energy) expected for self-organized criticality (e.g., Cheng et al 1996;Gögüş et al 1999Gögüş et al , 2000Prieskorn & Kaaret 2012). This might suggest that the total energy output (which scales as E 2 dN/dE) is dominated by the largest events -the rare giant flares (although it is possible that such giant flares may comprise a separate component that is not the high energy tail of the self-organized critical phenomenon and are isolated events).…”
Section: Discussionsupporting
confidence: 66%
“…In fact, the cutoff energy of the truncated icosahedron model with n = 60 nodes is higher than that of the regular dodecahedron model with n = 20. A cutoff feature was also found in the observations of SGR 1806−20 and SGR 1900+14 [9]. While the statistical significance of the observed cutoff is not high, bursts with the highest energy may correspond to avalanches enclosing the central neutron star.…”
Section: B Parameter Dependencesupporting
confidence: 52%
“…This value is consistent with the observations. According to Prieskorn and Kaaret [9], there is no difference between the power-law indices observed in high-and low-burst-rate regimes. This result may appear to contradict our CA model with ∆B dependence, but we found that cases with the same values of ∆B /B c are equivalent.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 2 more Smart Citations